2017
DOI: 10.1038/s41467-017-01856-y
|View full text |Cite
|
Sign up to set email alerts
|

Quenching protein dynamics interferes with HIV capsid maturation

Abstract: Maturation of HIV-1 particles encompasses a complex morphological transformation of Gag via an orchestrated series of proteolytic cleavage events. A longstanding question concerns the structure of the C-terminal region of CA and the peptide SP1 (CA–SP1), which represents an intermediate during maturation of the HIV-1 virus. By integrating NMR, cryo-EM, and molecular dynamics simulations, we show that in CA–SP1 tubes assembled in vitro, which represent the features of an intermediate assembly state during matur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
74
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 57 publications
(82 citation statements)
references
References 76 publications
(109 reference statements)
6
74
0
1
Order By: Relevance
“…This result implies that changes in the PPIP(122-125) motif do not prevent the formation of the six-helix bundle at the CA-SP1 junction and thus do not abrogate hexamer assembly. Interestingly, there does appear to be some cross talk between the PPIP(122-125) motif and SP1, as a mutation at residue 8 of SP1 (SP1-T8I [44,45]) results in conformational changes in the PPIP(122-125) loop (46).…”
Section: Discussionmentioning
confidence: 99%
“…This result implies that changes in the PPIP(122-125) motif do not prevent the formation of the six-helix bundle at the CA-SP1 junction and thus do not abrogate hexamer assembly. Interestingly, there does appear to be some cross talk between the PPIP(122-125) motif and SP1, as a mutation at residue 8 of SP1 (SP1-T8I [44,45]) results in conformational changes in the PPIP(122-125) loop (46).…”
Section: Discussionmentioning
confidence: 99%
“…During maturation, proteolytic processing of Gag yields cleavage products that reassemble to produce mature virions [123]. All-atom simulations proved invaluable in determining the structures of the immature HTLV-1 [124] and RSV [125] Gag lattices, as well as the HIV-1 capsid protein-SP1 peptide maturation intermediate (CA-SP1) [126]. Notably, simulations revealed that the CA-SP1 six-helix bundle exists in a dynamic helix-coil equilibrium, and that maturation-inhibiting drugs and mutations act by stabilizing a helical form of the bundle [126].…”
Section: Immature Particle Latticesmentioning
confidence: 99%
“…All-atom simulations proved invaluable in determining the structures of the immature HTLV-1 [124] and RSV [125] Gag lattices, as well as the HIV-1 capsid protein-SP1 peptide maturation intermediate (CA-SP1) [126]. Notably, simulations revealed that the CA-SP1 six-helix bundle exists in a dynamic helix-coil equilibrium, and that maturation-inhibiting drugs and mutations act by stabilizing a helical form of the bundle [126]. MD studies of CA-SP1 bound to inositol phosphates showed that these small molecules facilitate the formation of the six-helix bundle and, thus, promote assembly of the Gag lattice [127].…”
Section: Immature Particle Latticesmentioning
confidence: 99%
“…Damit reduziert sich die erforderliche Probenmenge um fast zwei Größenordnungen und es eröffnet sich die Möglichkeit, die Proteine in den Mengen, wie sie typischerweise in zellfreier Herstellung gewonnen werden, zu analysieren. Während >100 kHz MAS‐NMR‐Spektroskopie, zellfreie Proteinherstellung, NMR‐Spektroskopie an großen Komplexen und von Membranproteinen schon in der Literatur beschrieben wurden, zeigen wir hier, dass trotz der bereits hohen Komplexität jedes einzelnen dieser Elemente steht, deren Verbindung möglich ist und uns erlaubt hat, NMR‐Daten der DHBV‐SVPs mit guter Auflösung und Empfindlichkeit zu erhalten. Dies sollte die Untersuchungen dieser und ähnlich großer Membranproteinkomplexe, deren Strukturen bisher nicht aufgeklärt werden konnten, ermöglichen.…”
Section: Figureunclassified